The bar & beverage book - Katsigris, Costas; Thomas, Chris (Hoboken, N.J. : John Wiley & Sons, 2012)
"The Bar and Beverage Book explains how to manage the beverage option of a restaurant, bar, hotel, country club--any place that serves beverages to customers. It provides readers with the history of the beverage industry and appreciation of wine, beer, and spirits; information on equipping, staffing, managing, and marketing a bar; and the purchase and mixology of beverages. New topics in this edition include changes to regulations regarding the service of alcohol, updated sanitation guidelines, updates to labor laws and the employment of staff, and how to make your operation more profitable. New trends in spirits, wine, and beer are also covered"--
Includes index.
Keywords: Bartending